Enhancing Students' Reading Comprehension In Descriptive Text Through Directed Reading Thinking Activity (DRTA): A Classroom Action Research At The Tenth Grade Of SMA Negeri 6 Padangsidimpuan - Hutapea, Mutiara Cindy Tesalonika; Harputra , Yuswin; Harahap, Tinur Rahmawati (ETANIC Journal Of English Language Teaching And Applied Linguistics, 2025)
This research investigates the effectiveness of Directed Reading Thinking Activity (DRTA) in enhancing reading comprehension of descriptive texts among tenth-grade students at SMA Negeri 6 Padangsidimpuan. Using classroom action research with 32 students from Class X-1, the study implemented DRTA through a systematic approach of prediction, verification, and reflection. Initial assessment showed only 15.625% of students achieving scores above the Minimum Competency Criteria (KKM) of 75. Findings demonstrate significant improvement, with average scores increasing from 56.56 in pre-cycle to 71.91 in Cycle I and 83.34 in Cycle II. The percentage of students reaching KKM rose to 90.625% after Cycle II. DRTA effectively transformed reading into an interactive process, addressing key challenges of vocabulary deficiencies and low engagement. The findings highlight the importance of student-centered approaches in EFL reading instruction.